Modelling the atmospheric dispersion of radiotracers in small-scale, controlled detonations: validation of dispersion models using field test data - Thiessen, Kathleen M; Kuča, Petr; Helebrant, Jan; Hůlka, Jiří; Charnock, Thomas W; Chouhan, Sohan L; Ďúran, Juraj; Fuka, Vladimir; de With, Govert; Mancini, Francesco; Periáñez, Raúl; Tay, Bee Kiat; et al. (Journal of radiological protection, 2022)
A series of modelling exercises, based on field tests conducted in the Czech Republic, were carried out by the 'Urban' Working Groups as part of the International Atomic Energy Agency's Environmental Modelling for Radiation Safety II, Modelling and Data for Radiological Impact Assessment (MODARIA) I and MODARIA II international data compilation and model validation programmes. In the first two of these programmes, data from a series of field tests involving dispersion of a radiotracer,99mTc, from small-scale, controlled detonations were used in a comparison of model predictions with field measurements of deposition. In the third programme, data from a similar field test, involving dispersion of140La instead of99mTc, were used. Use of longer-lived140La as a radiotracer allowed a greater number of measurements to be made over a greater distance from the dispersion point and in more directions than was possible for the earlier tests involving shorter-lived99mTc. The modelling exercises included both intercomparison of model predictions from several participants and comparison of model predictions with the measured data. Several models (HotSpot, LASAIR, ADDAM/CSA-ERM, plus some research models) were used in the comparisons, which demonstrated the challenges of modelling dispersion of radionuclides from detonations and the need for appropriate meteorological measurements.
Keywords: monitorování radiace; jaderná energie; field test; teoretické modely; Radiation Monitoring; Humans; Radioisotopes; Models, Theoretical; radiotracer; dispersion modelling; lidé; Nuclear Energy; radionuklidy